(untitled) (Journal of Universal Science Research, 2024)
For many decades’ obesity has been one of the main risk factors for the development of cardiovascular pathology. Despite the efforts of scientists and physicians of various specialities, the burden of this pathology continues to increase its contribution to morbidity and mortality from cardiovascular disease. Numerous anthropometric criteria of obesity are well studied, simple and inexpensive means of diagnosing overweight in the population. However, their accuracy is relatively low. In particular, body composition, which is key to cardiovascular risk stratification, cannot be determined using these criteria. Despite the relatively short period of use of ultrasound methods for the diagnosis of obesity, convincing evidence of their high accuracy and effectiveness in predicting cardiovascular risk has already been obtained. Given the continuous improvement of ultrasound machines, these criteria should be incorporated into routine clinical and research practice. This literature review considers the main parameters used in ultrasound diagnosis of obesity, their contribution to the development of both traditional risk factors and directly cardiovascular diseases.